Motivating your R&D staff - Manners, George E. Jr.
George E. Manners, Jr., Joseph A. Steger and Thomas W. Zimmerer, in their RTM Classic, present the basics for generating the excitement they consider the essence of motivation for technical people.
Ten basic tenets form a body of practical knowledge for generating the excitement that is the essence of motivation for technical people.
In response to requests that RTM reprint articles that have drawn unusual reader response, we continue here a new feature entitled "RTM Classic." The first classic, "Lucky Alva," appeared in our July-August 1995 issue (pp. 28-30). Its author, Vladimir Haensel, imagined how Edison would have fared in trying to obtain funding for his electric light bulb idea in the modern corporate environment.-The Editor.
Keywords: R&D staff